Crescimento e produção do café Conilon irrigado por gotejamento subsuperficial com braquiária na entrelinha - Nascimento, Alan de Lima (2021)
Coffee is an important Brazilian agricultural commodity, with the varieties Coffea arabica (Arabica Coffee) and Coffea canephora (Conilon Coffee and robust), the most consumed coffees in the world. Given the importance of culture, technologies such as the use of subsurface dripping associated with the use of cover plants between the lines of the coffee tree have gained ground in the field, with the premise of achieving greater efficiency in the use of water and reducing damage caused by cultural treatments, increasing system life and reducing costs. Thus, the objective was to evaluate the production and vegetative growth of Conilon coffee genotype 153, managed with and without brachiaria between the lines, and with the use of a dripper at different depths in relation to the soil surface, in the northern region of Espírito Santo. The experimental design used was in randomized blocks (DBC), with four replications and five plants per plot, in a split plot arrangement, with the plot being the types of management between the lines of the coffee tree (with brachiaria and traditional), and the subplots depths dripper tube in relation to the soil surface (superficial, 0.08 m and 0.16 m). Growth evaluations were carried out on plants 11 months after transplanting, in three useful plants per plot every 60 days, totaling five evaluations. The measured response variables were: morphological, total growth, daily rates of growth of the orthotropic and plagiotropic branch and productivity and yield of processed coffee beans. The cultivation of brachiaria between the lines and the use of the subsurface dripper did not limit the growth rate of the coffee tree, both in the winter and in the summer. The use of subsurface drip provided greater vegetative growth of conilon coffee. The intercropping with the brachiaria associated with subsurface drip provided greater vegetative growth of the branches, but resulted in less productivity. Higher coffee bean yield was obtained when surface drip was used.